Are we making the same mistakes in fighting COVID‑19 as in past pandemics? Lessons from HIV show the urgent need to invest in HPSR - David Stuckler; Martin McKee; Alexander Kentikelenis (Sax Institute, 2021)
Are we repeating the mistakes of the human immunodeficiency virus (HIV) epidemic in our approach to combating coronavirus disease 2019 (COVID-19)? Is the world's emphasis on developing vaccines overshadowing investment in the health systems that can deliver them? We analyse a report on the politics of investing in health policy and systems research (HPSR) and conclude by outlining three critical actions, using the Stuckler-McKee model of social change in health. These are: exploiting a political window of opportunity; changing the conversation; and mobilising a campaign to drive the agenda. When implemented together, these actions could help accelerate investment in health systems to combat the immediate COVID-19 pandemic and prepare health systems for the next crisis.